Level of critical thinking of junior high school students in solving mathematical problems - Mellawaty Mellawaty; YL Sukestiyarno; Zaenuri Zaenuri; Isnarto Isnarto (Polyhedron International Journal in Mathematics Education, 2023)
Critical thinking ability is a crucial ability in mathematics, both at the elementary, secondary, or college level. However, this critical thinking ability is still low. Therefore, the researchers want to study the problem at what level the students are doing in solving mathematical critical thinking problems. The research method used a qualitative method, with the implementation analyzing students who deal with mathematical critical thinking ability problems. The study was conducted at one of the State Junior High Schools in Kroya District, Indramayu, West Java. As a result of the study, information was obtained about students who could not solve the problems presented in mathematical critical thinking ability problems, so they did not understand which strategies should be used to solve problems that could be solved.